2019
DOI: 10.1017/dmp.2019.11
|View full text |Cite
|
Sign up to set email alerts
|

Health and Health Seeking in Mosul During ISIS Control and Liberation: Results From a 40-Cluster Household Survey

Abstract: ObjectivesISIS seized Mosul in June 2014. This survey was conducted to assess health status, health needs, and health-seeking behavior during ISIS control and the subsequent Iraqi military campaign.MethodsForty clusters were chosen: 25 from east Mosul and 15 from west Mosul. In each, 30 households were interviewed, representing 7559 persons. The start house for each cluster was selected using satellite maps. The survey in east Mosul was conducted from March 13–31, 2017, and in west Mosul from July 18–31, 2017.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…A plethora of further analyses showed that refugee children are at particular risk for diseases such as depression, infections, or poorly managed chronic diseases [4,5,6,7]. We and others previously identified children arriving in Europe during the current crisis to be particularly vulnerable to physical trauma and infectious diseases during their flight [8,9,10,11,12,13]. Besides psychological and physical trauma during displacement, malnutrition, poor hygiene, and overcrowded living conditions further add to the particular risk of refugee children for increased morbidity [1,14].…”
Section: Introductionmentioning
confidence: 99%
“…A plethora of further analyses showed that refugee children are at particular risk for diseases such as depression, infections, or poorly managed chronic diseases [4,5,6,7]. We and others previously identified children arriving in Europe during the current crisis to be particularly vulnerable to physical trauma and infectious diseases during their flight [8,9,10,11,12,13]. Besides psychological and physical trauma during displacement, malnutrition, poor hygiene, and overcrowded living conditions further add to the particular risk of refugee children for increased morbidity [1,14].…”
Section: Introductionmentioning
confidence: 99%
“…Supply chains were interrupted. Some people hesitated to attend the remaining functional PHCCs as they doubted the medicines they might need would be present, or feared encounters with Al Hesba , the religious police [ 19 ]. Where services were able to adapt, there was usually a strong cohesion between communities and health facilities and committed health staff.…”
Section: Discussionmentioning
confidence: 99%
“…Some people hesitated to attend the remaining functional PHCCs as they doubted medicines they might need would be present, or feared encounters with Al Hesba the religious police. [18] Where services were able to adapt, there was usually a strong cohesion between communities and health facilities and committed health staff. Some patient consultations took place in the evenings at the homes of health workers, where people felt safer.…”
Section: Discussionmentioning
confidence: 99%